2003
DOI: 10.1007/s00216-003-1878-1
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Rayleigh scattering spectra for studying the interaction of aminoglycoside antibiotics with pontamine sky blue and their analytical applications

Abstract: In a weakly acid medium, some aminoglycoside antibiotics, such as kanamycin (KANA), gentamicin (GEN), tobramycin (TOB), and neomycin (NEO), or acid bisazo dye pontamine sky blue (PSB) can only produce very weak resonance Rayleigh scattering (RRS) signals. However, when the two agents react with each other to form the ion association complexes, the RRS intensity can be enhanced greatly and a new RRS spectrum and a significant enhancement of the RRS intensity in the wavelength range 350-600 nm can be observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…[24][25][26][27][28] In this work, we found that in a weak acid aqueous solution, the RRS for Sild alone as an organic cation or Evans Blue (EB), itself, as an organic anion was weak. However, when two agents reacted with each other to form ion-association complexes by virtue of electrostatic and hydrophobic interaction forces, the RRS intensity could be greatly enhanced and a new RRS spectrum was observed.…”
Section: 3mentioning
confidence: 99%
“…[24][25][26][27][28] In this work, we found that in a weak acid aqueous solution, the RRS for Sild alone as an organic cation or Evans Blue (EB), itself, as an organic anion was weak. However, when two agents reacted with each other to form ion-association complexes by virtue of electrostatic and hydrophobic interaction forces, the RRS intensity could be greatly enhanced and a new RRS spectrum was observed.…”
Section: 3mentioning
confidence: 99%
“…Since its first introduction to the study of the aggregation of porphyrins, using a conventional spectrofluorometer (8,9), the RLS technique has become a useful technique for the determination of biological macromolecules such as nucleic acids (10)(11)(12) and proteins (13)(14)(15). Moreover, this method has been used for the study and determination of drugs (16)(17)(18), inorganic ions (19)(20)(21) and surfactants (22). Among the RLS methods for determining drugs, most are based on the interaction of drugs with an RLS probe.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a RS spectral method for the determination of antibiotics at the level of 12.9-17.6 ng/mL has been reported (19), based on simple molecular interactions; the selectivity is not good. To improve the sensitivity and selectivity, we have coupled the complex reaction (20) and catalytic reaction (21) with a RS spectral method, with good results.…”
Section: Introductionmentioning
confidence: 99%